Preliminary Overview of the Economies of Latin America and the Caribbean 2012 - Nations Unies (United Nations, 2013)
This publication shows that the global economic crisis has had a negative, albeit not dramatic, impact in the Latin America and the Caribbean region. Global financial instability led to smaller inflows of short-term capital and a more volatile exchange rate in Brazil and Mexico, but eased pressures towards currency appreciation. Monetary policy was slightly expansionary. The fiscal position deteriorated in most countries, but fiscal policies have remained predominantly prudent. The region’s economy proved resilient, despite the global economic downturn. Employment and wages rose, with unemployment falling more among women than among men, but there are signs that growth in “quality” employment has slowed. The outlook for 2013 is again for lacklustre and uncertain external conditions.